Design, Content and Ecological Validity and Reliability of the Physical Activity and Sport Habits Questionnaire for Children Aged 8–12 Years in the Province of Gipuzkoa (Spain) - Aduna Badiola-Lekue; Irantzu Ibañez; Maite Fuentes; Javier Yanci; Oidui Usabiaga; Aitor Iturricastillo (Children)
Background/Objectives: This study aimed to develop a questionnaire to describe and diagnose the physical activity and sport (PAS) habits of 8–12-year-old schoolchildren, assessing its content, ecological validity and reliability, from a multidimensional perspective aligned with Global Matrix 4.0 indicators. Methods: The questionnaire design phase involved seven individuals from the university sector and sport managers from the Gipuzkoa Provincial Council. Seventeen experts later evaluated the questionnaire’s content and ecological validity. For reliability testing, 276 schoolchildren aged 8 to 12 completed the questionnaire twice, with a time interval of two weeks to two months. Statistical analyses included the Wilcoxon test to compare expert ratings, effect size and percentage change calculations for magnitude assessment, and McNemar, McN-Bowker or Wilcoxon tests to compare differences between initial and repeat responses. Cohen’s Kappa was used to assess agreement. Results: The initial battery of items, submitted to the validation process, comprised 31 items across 10 dimensions, derived from validated questionnaires and published works. Following content and ecological validity evaluations, modifications were made and nine items were removed due to improved wording, clarification of concepts, redundancy or lack of relevance. Expert quantitative analyses indicated improved overall questionnaire values. Reliability analysis revealed significant differences in five of the twenty-two items, though substantial agreement (from slight to almost perfect) was observed in twenty items. Conclusions: The study confirmed the questionnaire’s validity and reliability as a suitable tool for assessing PAS practices among 8–12-year-old schoolchildren in Gipuzkoa, Spain, in both Basque and Spanish languages.